Parasitic fibroid: case report and novel approach in reducing incidence of future cases - S., Sukainah; TK, Nasir; K., Zulkifli; R., Roziana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We report a case of parasitic fibroid which developed less than 1 year following laparoscopic myomectomy using power morcellation. Following this case, a novel approach in reducing the incidence of future parasitic fibroid is described.